Whole mitochondrial genome analysis in highland Tibetans: further matrilineal genetic structure exploration - Li, Xin; Zhang, Xianpeng; Yu, Ting; Ye, Liping; Huang, Ting; Chen, Ying; Liu, Shuhan; Wen, Youfeng (Frontiers in Genetics, 2023)
The Qinghai-Tibet Plateau is one of the last terrestrial environments conquered by modern humans. Tibetans are among the few high-altitude settlers in the world, and understanding the genetic profile of Tibetans plays a pivotal role in studies of anthropology, genetics, and archaeology. In this study, we investigated the maternal genetic landscape of Tibetans based on the whole mitochondrial genome collected from 145 unrelated native Lhasa Tibetans. Molecular diversity indices, haplotype diversity (HD), Tajima's D and Fu's Fs were calculated and the Bayesian Skyline Plot was obtained to determining the genetic profile and population fluctuation of Lhasa Tibetans.To further explore the genetic structure of Lhasa Tibetans, we collected 107 East Asian reference populations to perform principal component analysis (PCA), multidimensional scaling (MDS), calculated Fst values and constructed phylogenetic tree. The maternal genetic landscape of Tibetans showed obvious East Asian characteristics, M9a (28.28%), R (11.03%), F1 (12.41%), D4 (9.66%), N (6.21%), and M62 (4.14%) were the dominant haplogroups. The results of PCA, MDS and Fst were consistent: Lhasa Tibetans clustered with other highland Tibeto-Burman speakers, there was obvious genetic homogeneity of Tibetans in Xizang, and genetic similarity between Tibetans and northern Han people and geographically adjacent populations was found.In general, this study further shed light on long-time matrilineal continuity on the Tibetan Plateau and the genetic connection between Tibetans and millet famers in the Yellow River Basin, and further revealed that multiple waves of population interaction and admixture during different historical periods between lowland and highland populations shaped the maternal genetic profile of Tibetans.